The Assassination of Lieutenant Joe Petrosino: A Contested Symbol in the Mainstream and Italian-American Press in the Early 20th Century - Marina Cacioppo (Humanities, 2023)
Recently, scholars have looked at the ethnic press through a social constructionist lens, examining the process through which immigrants developed a sense of identity and the role of print culture in forming “imagined communities” (Anderson). Here, I analyze the coverage of the 1909 assassination of police Lieutenant Petrosino in both mainstream and Italian-American press and popular culture. This shocking event ignited a debate over the nature and origin of the Mafia and the dangerousness of the Italian community, a debate involving discourses of racial difference, immigration restriction, and the capability of Italians to assimilate. This debate became an important arena in which Italian immigrants defined themselves and their place in America. Italians were represented predominantly in the context of criminality, so immigrant writers constructed their own counter-representations in newspapers, re-coding stereotypes and negotiating a collective Italian-American identity. In the press, Petrosino became a contested symbol: on the one hand, of the rhetoric of the inclusiveness of the American melting pot and, on the other, of the possibility of redemption from the discredit that the actions of a small minority threw on the whole community.